Endovascular Treatment of Ruptured Wide-Necked Anterior Communicating Artery Aneurysms Using a Low-Profile Visualized Intraluminal Support (LVIS) Device - Xue, Gaici; Liu, Peng; Xu, Fengfeng; Fang, Yibin; Li, Qiang; Hong, Bo; Xu, Yi; Liu, Jianmin; Huang, Qinghai (Frontiers in Neurology, 2021)
Objective: To evaluate the safety and efficacy of low-profile visualized intraluminal support (LVIS) stent-assisted coiling for the treatment of ruptured wide-necked anterior communicating artery (ACoA) aneurysms. Methods: The clinical and angiographic data of 31 acutely ruptured wide-necked ACoA aneurysms treated with LVIS stent-assisted coiling between January 2014 and December 2018 were retrospectively reviewed. Results: All stents were successfully deployed. The immediate angiographic results were modified Raymond-Roy class I in 27 cases, modified Raymond-Roy class II in 2 cases, and modified Raymond-Roy class IIIa in 2 cases. Intraoperative thrombosis and postoperative aneurysmal rebleeding occurred in one case each. Two patients (6.5%) who were admitted due to poor clinical grade conditions died during hospital admission as a result of initial bleeding. Angiographic follow-up (mean: 12.9 months) was performed for 26 patients, the results of which demonstrated that 25 aneurysms were completely occluded and 1 was class II. The last clinical follow-up (mean: 25.3 months) outcomes demonstrated that 27 patients had favorable clinical outcomes and 2 had poor clinical outcomes. Conclusion: LVIS stent-assisted coiling for ruptured wide-necked ACoA aneurysms was safe and effective, with a relatively low rate of perioperative complications and a high rate of complete occlusion at follow-up.